Selected Lectures of the Meeting "Environment and Health: Messages from the Future"; Cagliari (Italy); October 26, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the Meeting "Environment and Health: Messages from the Future"; Cagliari (Italy); October 26th, 2024   The Meeting "Environment and Health: Messages from the Future" is a Satellite Meeting of the 20th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 23rd-26th, 2024.   LECT 1. MATERNAL MILK STEM CELLS: WHICH ROLE IN PERINATAL PROGRAMMING OF ADULT DISEASES? • G. Faa, G. Pichiri, P. Coni, M. Piras, M. Fraschini, A. Reali, V. Fanos (Cagliari, Italy; Philadelphia, Pennsylvania, USA) LECT 2. MICROPLASTICS, ENVIRONMENT AND CHILDREN HEALTH • S. Bernasconi (Parma, Italy) LECT 3. ENDOCRINE DISRUPTORS (EDs) AND PERINATAL PROGRAMMING • M.E. Street (Parma, Italy) LECT 4. THE LIFE MILCH PROJECT: UPDATES AND PERSPECTIVES • P. Palanza, V. Fanos, A.M. Papini, S. Perrone, T. Ghi, S. Paterlini, M.M. Brambilla, D. Baccolo, C. Scopa, A. Ardenghi, A.M. Shulhai, C. Caffarelli, F. Nuti, F. Fernandez, C. Sartori, F. Alberghi, B. Righi, M. Fontana, L. Filonzi, C. Petrolini, B. Piccolo, E. Turco, R. Pintus, C. Piras, S. Petza, A. Dessì, F. Nonnis Marzano, S. Angioni, S. Vitale, D. Ponzi, A. Pelosi, M.E. Street (Parma, Cagliari, Florence and Reggio Emilia, Italy) LECT 5. POTENTIAL OF TERPINEN-4-OL AS AN ADDITIVE FOR THE PREVENTION OF BACTERIAL INFECTIONS IN NEONATAL BREASTFEEDING • D. Romeo (Milan, Italy) LECT 6. KANGAROO CARE AND NEW HAND MANAGEMENT TECHNIQUES • M. Melis (Cagliari, Italy) LECT 7. POTENTIAL OF ESSENTIAL OILS IN THE MANAGEMENT OF MICROBIAL INFECTIONS • F. Mondello, M. Di Vito, M.L. Ricci (Rome, Italy) LECT 8. AFLATOXIN M1 IN MILK: SITUATION AND ANALYTICAL METHODS • E. Arletti (Modena, Italy) LECT 9. TOXICANTS AND TOXINS • C. Marzetti (Bologna, Italy) LECT 10. ONE HEALTH IN MEDICINE • A. Colangelo (Trento, Italy) LECT 11. EPIGENETIC MODULATION OF INFLAMMATION IN THE AGE OF POLLUTION • M. Greco, G. Terziani (Rivalta di Torino and Brescia, Italy)